Strategi Pengembangan Usaha Kedai Kopi Jumah di Denpasar Barat - NUGRAHA, I MADE WIRASATHYA; DEWI, NI LUH PRIMA KEMALA; UTARI, NI KADEK SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.2, Desember 2024, 2024)
Development Strategy for Kopi Jumah Coffee Shop in West Denpasar.  In the current era of globalization, coffee shop businesses are required to adapt to even the slightest changes in order to thrive. Kedai Kopi Jumah, located in West Denpasar, offers a cozy atmosphere and a wide variety of coffee beverages, including long black, americano, flat white, cappuccino, and cafe latte. The aim of this research is to ascertain the internal (strengths and weaknesses) and external (opportunities and threats) factors affecting the development process of Kedai Kopi Jumah and to determine alternative business development strategies based on SWOT analysis (strengths, weaknesses, opportunities, and threats). The results of the SWOT analysis have yielded four alternative strategies, namely: SO Strategy ("Expanding the use of social media platforms for promotional purposes and creating engaging content to broaden the market share"), ST Strategy ("Maintaining and enhancing the quality of Kedai Kopi Jumah's products" and "Fostering strong customer relationships by improving service quality and product innovation"), WO Strategy ("Collaborating with endorsement services to promote Kedai Kopi Jumah," "Partnering with online food ordering applications such as Gojek, Grab, and ShopeeFood," "Organizing events with coffee enthusiast communities to promote Kedai Kopi Jumah and build customer relationships," and "Extending Kedai Kopi Jumah's operating hours to reach a broader market segment"), and WT Strategy ("Introducing new menu variants to align with current trends favored by the public").